Design of e-advanced calculus - Voon B.W.N.; Wong L.S. (American Institute of Physics, 2025)
The pandemic Covid-19 accelerated the evolution of education 4.0. The online teaching and learning activities are promoted by movement control which had been enforced globally. Teaching and learning in engineering, which very much relied on practical and face-to-face by nature, are challenged by rapid process of adoption and adaptation by both learners and teachers. In this paper, such process is reported on one of the most challenging subjects in engineering education - advanced calculus. The design and strategy of teaching, the teaching process, the tools, the assessment, and students' feedback are discussed. Majority of the students were able to accept the new norm of teaching and learning, with a few still opt to resume to face-to-face learning. As for teacher, multiple platforms and delivery methods, including interactive methods are suggested to retain the attention and maintain the performance of the students. ? 2024 Author(s).